Diversity of endophytic fungi isolated from root of Paphiopedilum javanicum - ARI PITOYO; SOLICHATUN SOLICHATUN; ARTINI PANGASTUTI; SUGIYARTO SUGIYARTO (Society for Indonesian Biodiversity, 2026)
Abstract. Pitoyo A, Solichatun, Pangastuti A, Sugiyarto. 2026. Diversity of endophytic fungi isolated from root of Paphiopedilum javanicum. Biodiversitas 27 (3): d270304. https://doi.org/10.13057/biodiv/d270304. Understanding the intimate relationship between orchids and their fungal communities is essential for effective conservation. To address this, we investigated the root anatomy and fungal associates of Paphiopedilum javanicum, an endangered slipper orchid native to Java. Root samples comprising 75 segments collected from five montane habitats were examined microscopically and subjected to fungal isolation. The recovered isolates were identified through ITS sequencing, and their taxonomic placement was confirmed by phylogenetic analysis using the Neighbor-Joining method. Microscopy revealed peloton structures in cortical cells, with colonization levels varying among roots and tending to be patchy rather than systemic. Direct peloton isolation yielded no viable fungi, while root-segment and seed-baiting methods successfully isolated 23 fungi. ITS analyses revealed that most isolates belonged to Ascomycota (15 species in 10 genera), including Fusarium, Xylaria, and Nigrospora. Basidiomycota represented 7 species in 6 genera, among them two Ceratobasidium isolates recognized as orchid mycorrhizal fungi, along with lignicolous taxa such as Phanerochaete, Schizophyllum, Cubamyces, and Polyporus. A single Mucoromycota isolate (Umbelopsis) was also identified. These findings demonstrate that P. javanicum roots host a taxonomically diverse fungal assemblage comprising both putative mycorrhizal symbionts and a broad suite of opportunistic endophytes and saprotrophs. The coexistence of these guilds suggests ecological flexibility in fungal associations. This study provides the first integrated anatomical and molecular characterization of root-associated fungi in P. javanicum from Indonesia and establishes baseline data to inform symbiotic propagation and conservation strategies.